Gross anatomy and ultrasonographic images of the reproductive system of the Malayan tapir (Tapirus indicus). - K., Lilia; Yusoff, Rosnina; Haron, Abd Wahid; Zahari, Z. Zainal; Abraham, Mariana (Blackwell Publishing, 2010)
The Malayan tapir (Tapirus indicus) is the largest among the four tapir species and is listed as an endangered species. Ultrasound examination and description of the external anatomy of the female reproductive system of three adult females were performed, whereas the internal anatomy was investigated in necropsied samples of four adult females and one subadult female. Descriptions of the male external genitalia were conducted on one adult male. Gross examination revealed the presence of a bicornuate uterus. The uterine cervix is firm and muscular with projections towards its lumen, which is also evident on ultrasonography. The elongated and relatively small ovaries, which have a smooth surface, could not be imaged on ultrasonography, due to their anatomical position. The testes are located inside a slightly pendulous scrotum that is sparsely covered with soft, short hairs. The penis has one dorsal and two lateral penile projections just proximal to the glans penis.